The effect of emotional intelligence towards organizational commitment, job performance, and job satisfaction among employees at German company (Federal Autocars Sdn. Bhd) / Adlin Adnan - Adnan, Adlin (Faculty of Business and Management, 2015)
The present research was conducted at Federal AutoCars Sdn Bhd.Glenmarie. This research and study was conducted to know the effect of employees’ emotional intelligence towards organizational commitment, job performance and job satisfaction at Federal AutoCars Sdn Bhd. The problem faced by the most organization is to have efficient and quality employees in all departments. The major problem that can be seen is there are group of employees who tend to take less responsibility when dealing with their task. This sort of behavior basically caused by lack of emotional intelligence skills by the employees. This study is to know the level of emotional intelligence among employees, relationship between emotional intelligence towards organizational commitment, job performance, and job satisfaction among employees. Next, the aim of this study is to know which element is affected by emotional intelligence the most. Lastly, to find the alternatives to cure the problems that occurred. The data were taken from 110 respondents using convenience sampling and the results were analyzed and interpretations of relationships were made. It was found that there is a significant relationship between emotional intelligence and organizational commitment, and job performance. As for between emotional intelligence and job satisfaction, the relationship is insignificant. Lastly, The most element that is affected by emotional intelligence in job performance.